Harmonisasi Takwil dan Tafwid dalam Tafsir Tarjumān al-Mustafīd Karya Abdul Rauf al-Singkili: Telaah Kritis terhadap Ayat-Ayat Teologi - Azzah Riscilia, Safira; Ananta, Pramudia; Nikma, Sofiatun; Zaidanil Kamil, Ahmad (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2023)
This article confidently and diplomatically discusses Abdul Rauf al-Singkili's interpretation of theological verses, particularly those related to Istawā, Yadullah, and Ru'yatullah. Al-Singkili was a prominent scholar who lived in the 17th century AD in Aceh, Indonesia. His works became an important reference in Islamic studies at that time, especially his Tafsir work entitled Tarjumān al-Mustafīd, which was the first 30 juz Tafsir book in Indonesia. This Tafsir was also written during a theological debate in Aceh. This article confidently presents an intertextual analysis approach, inspired by Julia Kristeva, to interpret theological verses by al-Singkili. The analysis takes into account the socio-political and religious conditions of Acehnese society during that time. The author acknowledges the complexity of the subject matter and strives to present a balanced and diplomatic perspective. Based on the analysis results, it can be confidently stated that al-Singkili's interpretation of theological verses is heavily influenced by the Sunni school's method, which in turn has been shaped by the thoughts of al-Qushaiyshi and al-Kurani. This approach not only provides a more moderate response to the problems posed by the Wujudiyyah sect in the Aceh kingdom, but also showcases a diplomatic approach to theological discourse. This article makes a valuable contribution to the comprehension of al-Singkili's interpretation and his distinctive perspective on theological verses. The comprehensive analysis can serve as a source of inspiration and reference for researchers and academics interested in the field of Islamic studies and Qur'anic interpretation.